Comparison of three molecular subtyping techniques for Listeria monocytogenes Comparación de tres técnicas para subtipificación molecular de Listeria monocytogenes - Londero, Alejandra (2019)
Listeria monocytogenes is a foodborne pathogen. The recent alert for L. monocytogenes in vegetables from Argentina warns about the importance of reinforcing its isolation, characterization and subtyping in food, clinical and environmental samples. The aim of the present study was to compare the discriminatory power of enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR), automated ribotyping and pulsed-field gel electrophoresis (PFGE) to subtype strains of L. monocytogenes isolated from Argentine meat and environmental samples. Simpson's Diversity Index (DI) was calculated on the basis of based on the dendrograms obtained in the by cluster analysis, showing the following discriminatory power: ApaI-PFGE (0.980), AscI-PFGE (0.966), ribotyping (0.912), ERIC-PCR (0.886). The ID values between ApaI- and AscI-PFGE and between ribotyping and ERIC-PCR were not significantly different. Of the three techniques evaluated, PFGE showed the highest discriminatory power. However, the subtyping techniques should be accompanied by effective food monitoring strategies and reliable clinical and epidemiological studies.